Distribution Shop Center (Distro) Local Brand Clothes and Skate Playges in Kuta Utara, Badung, Bali - Ranubhuana, Ni Rara; Adhika, I Made; Budjana, I Gusti Bagus (Journal of A Sustainable Global South; Vol 1 No 2 (2017): August 2017DO - 10.24843/jsgs.2017.v01.i02.p01, 2017)
The centre of clothing distro and skatepark are buildings that are included in commercial and business functions. The centre of clothing distro is community of several clothing brands that have their own distro. The function of distro is to display and sell their products. Various concepts and idealism are offer from every clothing brands. Some concepts are offer such as music, skateboarding, custom motorbikes, surfing, tropics, and other concepts. The concepts of the brand will affect the interior concept that will applicated. The goal is to provide the identity and characteristics of distro, so that attract consumers to come and buy some products. The industrial concept interior is very suitable to be apply in a dis-tro. The material in industrial concept shows natural impression of material such as expose bricks, concrete, floor and some finishing marerials while still displaying the original texture. This makes the industrial concepts more affordable but requires high creativity, so that it is suitable to be apply in a distro. This concept will give a masculine impression, rough but still comfortable. The collaboration of the industrial concept with the concept with the concept of clothing brand can be apply by adding some decoration and artwork that related with the concept. Index Terms — industrial, distro, interior.